Education-Based Mobile Apps Platform in Patients Undergoing Surgery: A Systematic Review - Sariati Sariati; Esti Yunitasari; Laily Hidayati (Universitas Airlangga, 2020)
Introduction: Providing sufficient information during a pre-operative helps patients understand their condition and plan of care, to identify and manage potential complications, and to reduce hospital readmission. New innovation mobile application platforms put education in the hands of patients and their families. The aim of study was to investigate the effect of mobile application education in patients undergoing surgery.Methods: A systematic review study was based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyzes) with article sources using the Scopus, Science Direct, PubMed and ProQuest databases. Limited to the last 5 years (2015-2020) using English as well as full-text articles. This was done using a combination of keywords and Boolean operators (AND and OR). Keywords used in searching are “Education” “Pre-operative Education”,